Thymidine kinase-1/CD31 double immunostaining for identifying activated tumor vessels. (2nd January 2019) - Okamura, S.; Osaki, T.; Nishimura, K.; Ohsaki, H.; Shintani, M.; Matsuoka, H.; Maeda, K.; Shiogama, K.; Itoh, T.; Kamoshida, S.
ABSTRACT: Although angiogenesis plays a crucial role in cancer growth and progression, no reliable method for assessing angiogenesis in tumor tissue sections currently is available. Using biomarkers with high specificity for proliferating endothelial cells could help quantify angiogenic activity. Thymidine kinase-1 (TK1) is an enzyme involved in the salvage pathway of DNA synthesis and its activity is correlated with cell proliferation. We investigated the use of double immunostaining for TK1 and CD31 for identifying activated tumor vessels. Differences in TK1/CD31 positive vessel rates (PVRs) between tumor and adjacent normal tissues were evaluated in 39 colorectal carcinoma (CRC) samples and compared with those of Ki67/CD31 double stained tissues. Mean TK1/CD31 PVR (23.6%) in CRCs was 13.9 fold greater than in adjacent normal tissues (1.7%)). By comparison, mean Ki67/CD31 PVR in CRCs was 20.0%, i.e. only 4.8 fold greater than in normal tissues (4.2%). Also, mean TK1/CD31 PVR in normal tissues was significantly less than mean Ki67/CD31 PVR. Our findings indicate that double immunostaining for TK1/CD31 can detect activated tumor vessels more accurately than staining for Ki67/CD31 and potentially could identify tumors that will respond to anti-angiogenic therapy.